Structural, morphological, and magnetic properties of NiF2 assisted growth of Ni-multi walled carbon nanotubes. (2022) - Devadoss, Manimegalai; Vinothkumar, G.; Jerries Infanta, J.; Pandurangan, A.; Venkatesh, R.; Arumugam, S.; Sivaprakash, P.
Abstract: This paper reports the synthesis and magnetic properties of NiF2 assisted growth of multi-walled carbon nanotubes. Ni-Multi-Walled Carbon Nanotubes (Ni-MWCNT) were synthesized by catalytic decomposition of Xylene (C8 H10 ) and NiF2 (as a precursor for metallic Ni) using Chemical Vapor Deposition (CVD). The presence of graphitic carbon crystallization and a dominant metallic nickel phase is confirmed by XRD and Raman analysis. The in-situ formation of Ni nanoparticles from NiF2 precursor successfully aids the growth of Ni-MWCNTs. The diameter of synthesized Ni-MWCNT was measured to be around 100 nm. Ni-MWCNT exhibit a weak ferromagnetic property due to the presence of metallic Ni residues.